2014
DOI: 10.1136/bjophthalmol-2014-305236
|View full text |Cite
|
Sign up to set email alerts
|

Changes in angle of optic nerve and angle of ocular orbit with increasing age in Japanese children

Abstract: PurposeTo study changes in the opening angle of the optic nerve and the angle of the ocular orbit with increasing age in normal Japanese children.MethodsWe studied 147 normal children (aged 6 months to 18 years) who had undergone CT as a diagnostic procedure. Measurements were performed on axial CT images that included the entire optic nerve of both eyes. The opening angle of the optic nerve was defined as the angle formed by the intersection of a line running through the left optic nerve and a vertical line p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…CT imaging has been widely used for many years to observe inner structure from various angles, accurately measure orbital parameter values, and evaluate facial asymmetry [30]. Previous studies [2,31,32] have evaluated different methods of ocular protrusion measurement in a two-dimensional plane. However, typically, the apex of the cornea is not in the same CT imaging plane as the most posterior part of the lateral margin of the orbit, leading to some uncertainties or errors during measurements.…”
Section: Discussionmentioning
confidence: 99%
“…CT imaging has been widely used for many years to observe inner structure from various angles, accurately measure orbital parameter values, and evaluate facial asymmetry [30]. Previous studies [2,31,32] have evaluated different methods of ocular protrusion measurement in a two-dimensional plane. However, typically, the apex of the cornea is not in the same CT imaging plane as the most posterior part of the lateral margin of the orbit, leading to some uncertainties or errors during measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the change in the orientation of the optic nerve head with increasing age in myopic children. 23 Future studies may specifically address the change in the rotation of the optic nerve head in children in dependence on the refractive error.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the angle of the orbit measured between the medial and lateral orbital wall decreased until the age of 1 year, with little change noted thereafter. 11 13 The biorbital angle used in our study was approximately equal to the total amount of the right and left angles measured by Escaravage and Dutton. 12 Furthermore, our results showed that the biorbital angle became narrower at the age of 1 year and then remained unchanged, which matches with the previous results of Escaravage and Dutton.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, this decrease in the opening angle of the orbit with increasing age was statistically significant. 13 These findings additionally suggest that the decrease in the opening angle of the orbit may contribute to the decrease in the exodeviation that is seen in 70%–80% of normal newborns. 14 Furthermore, this morphological change might provide important information on the management of strabismus in infants.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation